2008
DOI: 10.1099/vir.0.2008/003103-0
|View full text |Cite
|
Sign up to set email alerts
|

Negative modulation of the chicken infectious anemia virus promoter by COUP-TF1 and an E box-like element at the transcription start site binding δEF1

Abstract: Expression of enhanced green fluorescent protein (EGFP) under control of the promoterenhancer of chicken infectious anemia virus (CAV) is increased in an oestrogen receptorenhanced cell line when treated with oestrogen and the promoter-enhancer binds unidentified proteins that recognize a consensus oestrogen response element (ERE). Co-transfection assays with the CAV promoter and the nuclear receptor chicken ovalbumin upstream promoter transcription factor 1 (COUP-TF1) showed that expression of EGFP was decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Direct alignment between the partial NTR sequences of GyV6 and it’s the closest matches in HGyV/AGV2 and GyV3 revealed that 16 to 18 nucleotides were likely not sequenced. The GyV6 NTR possessed four tandem repeats of a CAV promoter (TGTACAGGGGGGGT ACGTCA ) containing a putative estrogen-response element ( ACGTCA ) that can upregulate transcription (Miller et al, 2005) and can be negatively regulated by COUP-TF1 (Miller et al, 2008). Four copies of this promoter element are found in CAV and HGyV/AGV2, while only one copy in GyV3.…”
Section: The Studymentioning
confidence: 99%
“…Direct alignment between the partial NTR sequences of GyV6 and it’s the closest matches in HGyV/AGV2 and GyV3 revealed that 16 to 18 nucleotides were likely not sequenced. The GyV6 NTR possessed four tandem repeats of a CAV promoter (TGTACAGGGGGGGT ACGTCA ) containing a putative estrogen-response element ( ACGTCA ) that can upregulate transcription (Miller et al, 2005) and can be negatively regulated by COUP-TF1 (Miller et al, 2008). Four copies of this promoter element are found in CAV and HGyV/AGV2, while only one copy in GyV3.…”
Section: The Studymentioning
confidence: 99%
“…DeltaEF1 factor, a zinc finger protein, is implicated in the regulation of a lot of viral and cellular genes with functionally diverse roles [21,22]. Through binding directly to the promoters, it represses transcription of epithelial splicing regulatory protein 2 [23], E-cadherin [24] and Plakophilin 3 genes [25], and suppresses promoter activity of chicken infectious anemia virus [26] as well. Here, we confirmed that deltaEF1 is also transcription repressor of pIFIT2 gene.…”
Section: Discussionmentioning
confidence: 99%
“…The particular infection form of latency or pseudo-latency might also lead to difficulties to detect the infecting viruses. In these circumstances the infecting viruses are present in distinctively minute amounts, at least until reactivation, as in the case of herpesviruses, like ILTV (Guy et al, 1991;Hughes et al, 1991) and circoviruses, like CAV (Miller et al, 2008). In commercial flocks the infection is not synchronous, and the timing of sampling is dictated by the appearance of clinical signs in conjunction to other factors.…”
Section: The Sampling Timingmentioning
confidence: 99%